What Neuroimaging and Brain Localization Can Do, Cannot Do, and Should Not Do for Social Psychology. - Willingham, Daniel T.; Dunn, Elizabeth W. (Journal of Personality & Social Psychology, 2003)
Interest in bridging social psychology and neuroscience has seen a significant upsurge. Much of this interest has centered on brain localization|Amthe attempt to relate psychological events to locations of brain events. Although many articles have sought to localize brain activity that supports social behavior, scant attention has been paid to the specific methods to be used in integrating brain localization data into psychological theory. The authors describe 4 strategies psychologists can use to integrate brain localization data and psychological theory, and they consider whether social psychology presents special considerations in the use of these strategies. They conclude that brain localization offers a useful tool for some but not all problems in social psychology, and they discuss the types of problems for which it may and may not prove useful. Reprinted by permission of the publisher.